NSI: A major occupational hazards among the health care workers in Nepal - Mondal, Jaita (International Journal of Occupational Safety and Health, 2013)
A percutaneous piercing wound as in needle stick injury is a typically set by a needle point, but possibly also by other sharp instruments or objects. These events are of concern because of the risk to transmit blood-borne diseases through the passage of the hepatitis B virus (HBV), the hepatitis C virus (HCV), and the Human Immunodeficiency Virus (HIV), the virus which causes AIDS. The present study was done to determine the risk status regarding NSI among health care workers of Private Hospitals, Pokhara, Nepal. Samples were selected through purposive sampling. Self administered questionnaire & risk assessment tool were used to collect data. Study revealed that majority of health care workers were females (93%) with mean age of 22.66 years (±3.1). Sixty eight percent had got NSI, among them 41% had NSI more than 2times in life. Maximum NSI cases happened either by recapping of the needle (18%) or during disposal of sharps (16%) or while transferring a body fluid (blood) to a specimen bottle (15%). The study concludes that majority of health workers had NSI more than two times which denotes NSI is a major occupational hazard. Cases happened either by recapping of the needle or during disposal of sharps or while transferring a body fluid to a specimen bottle. DOI: http://dx.doi.org/10.3126/ijosh.v3i1.9098 International Journal of Occupational Safety and Health, Vol 3 No 1 (2013) 22-25